On translation of film titles from German into Polish - Feret, Magdalena Zofia; Feret, Andrzej S. (Papers in Linguistics, 2022)
The article focuses on current tendencies in translation of film titles from German to Polish. In order to determine which translation tendencies prevail contemporarily, an analysis was performed concerning titles of German films shown during the so called Week of German Film since 2010 and their Polish counterparts. The aim was to identify translation strategies applied to render these film titles. Results of the analysis presented here were also compared with results of the analysis of film titles translation from English into Polish.